Closing the academy–Business gap by building intellectual capital in professional formation - Vélez-Rolón, Adela M.; Pulido López, Alejandra; Méndez-Pinzón, Manuel; Neira-Bermudez, Diego (Frontiers in Sociology, 2023)
The accelerated advance of technology, market pressures, globalization, and more recently the emergence of covid 19, show the urgent need to find educational models that respond to these realities, but at the same time contribute to improving the employability levels of young people and promote economic growth. This research analyzes how the professional training model, where two learning spaces, the academy, and the company, are combined, promotes the closing of gaps and economic growth, through the development of an intellectual capital that arises from this relationship, in an emerging economy such as the Colombian one. The methodology used corresponds to the qualitative approach, where the vision of the different actors involved in the training process at the undergraduate level in Colombia was analyzed through semi-structured interviews, focus groups, and documentary analysis. The results show 5 major elements that must be taken into account for the formation of the intellectual capital necessary for the success of the relationship and the reduction of the gaps between academia and business, thus enhancing economic growth and a determining factor for the fulfillment of SDG 8 "decent work and economic growth".